Síntese, caracterização e estudo das propriedades magnéticas do Zn(1-x)EuxO (0,0 ≤ x ≤ 0,035) produzido por reação de combustão - Soares, Mônica Pereira (2013)
Nanocrystallitics of Zinc Oxide containing different amounts of Europium (Zn(1-X)EuxO – it being 0,0 ≤ x ≤ 0,035) were synthesized by a combustion reaction, with the aim of evaluating the effect of the concentration of Eu3+ in magnetic properties, after obtained. The chemical composition was determined by energy dispersive spectroscopy, X-ray (EDS). The structural characterization was performed by X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetrics Analysis (TGA), Spectroscopy Photoelectrons Excited by X-Rays (XPS) and Transmission Electron Microscopy (TEM). Crystallinestructure powders of ZnO in wurtzita were formed after the thermical treatment at 550°C about one hour, with average size crystallites of 20 nm. The X-Ray Diffraction results showed presence of diffraction peaks of well-defined of ZnO primary characteristic phase and traces of oxide Europium (Eu2O3) as secondary stage for samples doped with 3.5% of Eu3+. The analyzes showed the magnetic samples exhibit ferromagnetism at room temperature dependent content of ions Eu3+, but for the sample doped with 3.5% Europium the magnetization drops considerably, due to the formation of Oxide Europium (Eu2O3) non-magnetic. This fact suggests that the ferromagnetism of samples is associated with the Eu3+ ions, it is occupying the interstices of matrix semiconductor wafer.